2018
DOI: 10.1038/s41375-018-0216-8
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum and functional validation of PSMB5 mutations in multiple myeloma

Abstract: Despite an increasing number of approved therapies, multiple myeloma (MM) remains an incurable disease and only a small number of patients achieve prolonged disease control. Some genes have been linked with response to commonly used anti-MM compounds, including immunomodulators (IMiDs) and proteasome inhibitors (PIs). In this manuscript, we demonstrate an increased incidence of acquired proteasomal subunit mutations in relapsed MM compared to newly diagnosed disease, underpinning a potential role of point muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
100
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 35 publications
0
100
0
Order By: Relevance
“…We provide a validated sequencing approach, including the detection of recurrent translocations, that will increase the diagnostic value of such techniques. Moreover as the whole genome and complete RNA expression is covered our approach can rapidly incorporate novel resistance mechanisms such as PSMB5 mutations [49] . And novel clinical master protocols rely on genomic data to decifer actionable genomic alterations and allow the allocation of patients to effective treatment options [50] .…”
Section: Discussionmentioning
confidence: 99%
“…We provide a validated sequencing approach, including the detection of recurrent translocations, that will increase the diagnostic value of such techniques. Moreover as the whole genome and complete RNA expression is covered our approach can rapidly incorporate novel resistance mechanisms such as PSMB5 mutations [49] . And novel clinical master protocols rely on genomic data to decifer actionable genomic alterations and allow the allocation of patients to effective treatment options [50] .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, very few nonrecurring mutations or aneuploidies were found in proteasome subunit genes in our cohort, confirming their rarity. 16,55 We assessed high-risk genetic 3 ), double-hit events, 11 apolipoprotein B mRNA editing enzyme, catalytic polypeptide-like (APOBEC) signature contribution, 13 TP53 mutations, 9 and CRBN pathway mutations 15 and found that at least 1 such event was present in 65% of patients ( Figure 2D).…”
Section: Genomic Makeup Of Treatment-resistant Samplesmentioning
confidence: 99%
“…[9][10][11][12][13] In relapsed or refractory MM (RRMM), a small number of mutations implicated in resistance to PIs or IMiDs have been identified through custom targeted gene panels or in occasional patients. [14][15][16] These mutations have been validated in in vitro models, but their clinical relevance needs additional study. Expression levels and splice isoforms of the IMiD target CRBN have been proposed to mediate resistance to those drugs, but results are conflicting and are not ready for the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies suggest that cases retain a significant heterogeneity, with subclones showing expansion or reduction based on the type of treatment, increased number of mutations, copy-number abnormalities, complex rearrangements and contribution from novel mutational signatures (17,23,34,35,96). Targeted sequencing studies have highlighted increasing prevalence of mutations conferring resistance to IMiDs (particularly in CRBN, IKZF1, IKZF3) and PIs (PSMB5, PSMB8, PSMB9, PSMD1, and PSMG2) (62,128). However, mutated cases are still a great minority and mutations are often subclonal, suggesting that while functionally relevant, the clinical impact of these mutations and their utility to guide further treatment will need validation.…”
Section: Relapsed and Refractory Myelomamentioning
confidence: 99%